Comparing self-reported reactogenicity between adolescents and adults following the use of BNT162b2 (Pfizer-BioNTech) messenger RNA COVID-19 vaccine: a prospective cohort study. (March 2022) - Chan, Edward Wai Wa; Leung, Miriam Tim Yin; Lau, Lauren Ka Wun; Leung, Janice; Lum, Dawn; Wong, Rosa Sze-Man; Li, Xue; Chui, Celine Sze Ling; Wan, Eric Yuk Fai; Wong, Carlos King Ho; Chan, Esther Wai Yin; Ip, Patrick; et al.
HIGHLIGHTS: Marked age differences in adverse reaction risks from BNT162b2 vaccination Moderately increased risks from BNT162b2 in adolescents compared with adults Self-reported adverse reactions peaked on the first follow-up day after vaccination ABSTRACT: Objectives: Although clinical data have shown that the BNT162b2 vaccine, which is widely used in many countries, is safe and effective as a protection against the SARS-CoV-2 infection, extant research in adverse reactions using real-world data of various sociodemographic characteristics is scant. Methods: We conducted a prospective cohort study to compare age differences in self-reported reactogenicity of BNT162b2 in Hong Kong. A total of 1, 516 participants were intensively followed up for two weeks following both doses of BNT162b2 vaccination, during which their basic demographic, health conditions, and medication information were collected. Results: Results from the generalized mixed model showed that compared with adults aged 18 to 59 years, older adults aged 60 years or above had a lower risk of adverse reactions and adolescents aged 12 to 17 years had a moderately higher risk. Conclusions: Results of this study should be informative to parents considering BNT162b2 vaccination for their children in that moderately increased reactogenicity compared with adults is anticipated.